Clinical results of the use of mitotane for adrenocortical carcinoma - Kasperlik-Zaluska,A.A. (2000)
Mitotane (o,p'-DDD) acts mainly as an inhibitor of intramitochondrial pregnenolone and cortisol synthesis. Its adrenolytic effect depends on metabolic activation due to conversion to o,p'-DDA and o,p'-DDE. The drug has been used for 40 years in the treatment of adrenocortical carcinoma, mainly its regional and metastatic stage, as an adjuvant to surgical resection of the tumor. In the medical literature there are controversial opinions about its efficacy for the treatment of adrenocortical carcinoma. In our experience, mitotane administered immediately after surgery appeared to be much more efficient than when administered later. We have administered this drug in all cases of microscopically confirmed adrenocortical carcinoma, irrespectively of stage at the time of surgery, for fear of a false too optimistic classification. In our series of 82 patients with adrenocortical carcinoma, 59 patients have been treated with mitotane, 32 of them immediately after surgery, and 27 with a delay of 2 to 24 months. Today there are 18 survivors in the group of patients treated with mitotane soon after the operation and only 6 survivors in the group receiving mitotane with a delay. All patients were simultaneously given replacement therapy. Undesired effects of mitotane administration included increased aminotransferase and alkaline phosphatase activity, decreased white cell, platelet or red cell number, and myasthenia. Furthermore, we used mitotane with good results in Cushing's syndrome of non-malignant origin as pre-treatment before surgery or in long-term treatment for patients with poor tolerance of other adrenal inhibitors.